PRAKTIK MENGKAFANI JENAZAH UNTUK SISWA SMK NEGERI 2 SANGATTA UTARA SEBAGAI BAGIAN DARI PENDIDIKAN FARDHU KIFAYAH - Nur Muhabibudin; Muhammad Syahrul Ramadhan; Anggara Prima (Jurnal Pelita Pengabdian Masyarakat, 2024)
This practical training on shrouding a corpse for students of SMK Negeri Sangatta Utara aims to provide practical training to students of SMK Negeri 2 Sangatta Utara in the skill of shrouding a corpse as part of the educational knowledge of fardhu kifayah. Through this activity, we hope to make a significant contribution in the character building of students, especially in increasing their social awareness and understanding of the important fardhu kifayah obligations in society. This activity uses interactive learning methods of discussion, question and answer, and theoretical presentation related to the importance of fardhu kifayah. The form of the activity is direct practice of practicing the skills of shrouding a corpse using appropriate media and tools. The training was delivered in theory and practice, focusing on the active involvement of students in each training session. Direct simulation in the field to ensure students can master the required skills. Activities take place over two weeks, with weekly training sessions. The first week was a basic introduction to fardhu kifayah, an introductory session on fardhu kifayah, the role and importance of shrouding the dead in the lives of Muslims, as well as a discussion on the procedures for shrouding the dead. The second week is practical training on shrouding the body, learning and practicing directly shrouding the body, from preparation to the process of shrouding the body with the correct procedure.